Kandungan Fitokimia Kulit Buah Jeruk Siam (Citrus nobilis Lour. var. microcarpa) Sehat dan Berpenyakit CVPD di Desa Catur, Kintamani Menggunakan GC-MS (Gas Chromatography-Mass Spectrometry) - Thanur, Steven; Wirawan, I Gede Putu; Phabiola, Trisna Agung (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024)DO - 10.24843/AJoAS.2024.v14.i03.p12, 2024)
Phytochemical Content of Healthy and Infected by Citrus Vein Phloem Degeneration Siam Citrus ( Citrus nobilis Lour. var. microcarpa ) Peels in Catur Village, Kintamani Using GC-MS ( Gas Chromatography - Mass Spectrometry ). Siam citrus ( Citrus nobilis Lour. var. microcarpa ) is one of the potential plants because it is widely developed in Bali and its taste is favored by consumers. The productivity of Siam citrus plants in Indonesia is still inadequate because it is often infected by Citrus Vein Phloem Degeneration (CVPD) caused by the Literobacter bacteria. The purpose of this study is to determine the difference content of phytochemical compounds of Healthy Siam citrus and Infected by Citrus Vein Phloem Degeneration citrus peel extract and the use of phytochemical compounds contained. Phytochemical analysis was performed with Gas Chromatograhy- Mass Spectrometry (GC-MS). The GC-MS analysis result showed that there was difference phytochemical compounds of Healthy Siam citrus and Infected by Citrus Vein Phloem Degeneration citrus peel extract. Healthy Siam citrus peel contain compounds such as Limonene, Cholestan-3-ol, 4',5,7,8-Tetramethoxyflavone, Beta-Elemene,5-Hydroxymethylfurfural, Octanal, Humulene, Noanal, Decanal, Perillartine, Citronellal, and Carveol. While the siam citrus peel infected by Citrus Vein Phloem Degeneration contains compounds such as Glycerin, 1,2- Cyclohexanediol,1-methyl-4-(1-methylethenyl), Benzoic Acid, Benzofuran, 2,3-dihydro-, 3,4-Altrosan, 2-Propenoic acid, 3-(4-hydroxy-3-methoxyphenyl), 5- Desmethysinensetin, Ferullic Acid, Furan, Itaconic Anhydride, Cyclohexane, 1-ethenyl-1-methyl-2,4-bis (1-methylethenyl)-, L-Carvone, n-Hexadecanoic acid. The presence of differences in secondary metabolites is caused by plants when exposed to biotic stress or disease, plants will produce more phytochemicals that used for mechanical defense of plant in nature.